2014
DOI: 10.3329/bje.v2i1.19589
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends in Pediatric Robotic Surgery

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 120 publications
(153 reference statements)
0
16
0
3
Order By: Relevance
“…The period during which a surgeon finds that the procedures are more difficult, take longer, and there is potentially a higher rate of complications and less effectiveness due to inexperience, which is called the learning curve (60). The use of robot assistance dramatically decreases the learning curve, because overcome the limitations of conventional laparoscopy (31, 3840). Our console surgery times have evolved in 19 pyeloplasties and in 26 fundoplications, with a decrease of 50% and of almost 52%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The period during which a surgeon finds that the procedures are more difficult, take longer, and there is potentially a higher rate of complications and less effectiveness due to inexperience, which is called the learning curve (60). The use of robot assistance dramatically decreases the learning curve, because overcome the limitations of conventional laparoscopy (31, 3840). Our console surgery times have evolved in 19 pyeloplasties and in 26 fundoplications, with a decrease of 50% and of almost 52%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Trends in the literature indicate that pediatric robot-assisted minimally invasive surgery is continuing to be globally utilized (1523, 3134). Numerous case reports, case series, and comparative studies have unequivocally demonstrated that robotic surgery in children is safe (35).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If conventional laparoscopy is used, the reconstructive and complex procedures are very challenging, and long periods of time are necessary to acquire the appropriate skills and confidence, vs. robotic surgery, the learning curve is shorter [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The benefits include the optimisation of resources in health systems and, regarding patients, shorter and less painful post-operative care, less tissue trauma, shorter hospital stays and faster recovery, allowing for a swifter return to daily life [1][2][3][4]. However, MIS also has some drawbacks [5,6], mainly related to spatial and technical limitations, that must be addressed with tremendous specialised training in specific MIS skills.…”
Section: Introductionmentioning
confidence: 99%